PENGARUH OPINI AUDIT, PROFITABILITAS, UKURAN KAP, DAN UKURAN PERUSAHAAN TERHADAP KETEPATAN WAKTU - Faizah, Wynne Nurul; Mulyani, Mulyani (Politeknik Negeri Lhokseumawe, 2023)
The occurrence of several phenomena of company delays in submitting their financial reports over the past three years has increased. In addition, the Covid-19 phenomenon also affects many aspects and causes companies to be late in reporting their financial statements. The purpose of this study is to prove whether audit opinion, profitability, public accounting firm size, and company size can affect the timeliness of submitting financial reports in manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2021 period. The sampling technique used in this study is a non-probabilistic sampling technique. The conclusion of this study shows that profitability has a negative and significant effect on the timeliness of financial report submission, company size has a positive and significant effect on the timeliness of financial report submission, while audit opinion and KAP size have no significant effect on the timeliness of financial report submission.Keywords: timeliness, audit opinion, profitability, size of public accounting firm, company size.